Femicide: The Crime Stated from the Perspective of Girls and Boys - Arrobo Andrade, Catalina (2022)
This paper intends to highlight the perceptions of children who experience their mother’s violent death. It can be assumed that people’s lives change after such a traumatic event. However, it is all too common that actions undertaken after violent crimes are mainly focused on the adults involved in the event. However, what happens to children when the femicide of their mother occurs? This issue leaves many unanswered questions requiring serious analysis and a deep, respectful, and consistent reflection on the children’s needs. In the following paper, I analyze the importance of “lending an ear” to the emotions of children after such a traumatic event to better understand the magnitude of the impact they suffer and the importance of having comprehensive protection mechanisms for their fundamental human rights.